Contribution of migration to replacement of population in Turkey - Ediev, Dalkhat M; Yüceşahin, Mustafa Murat (Migration Letters, 2016)
Relationship between migration and replacement of population has attracted a great deal of scholarly attention. Migration is considered to be a key factor in the growth and replacement of populations. Net migration sometimes exceeds natural change and drive population growth. Migration can compensate for missing births in low-fertility areas, provinces, or countries. Although past and recent general fertility trends, regional inequalities, and migration patterns in Turkey have been well documented through demographic surveys and censuses, the relationship between migration and the replacement of population by region in the country has not been adequately examined. Thereby, in this study, we explore the contribution of migration to the replacement of population in Turkey. Turkey’s regions, at the NUTS 1 level, are very diverse in their levels of fertility and migration, which makes it very interesting to study the two processes in tandem. We use a recently proposed methodology of studying the population replacement levels through the indicators of Combined Reproduction and Times to Half-Replacement, which can be computed from limited data and offers good insights into the demographic consequences of a given combination of fertility and migration levels.